2017
DOI: 10.1111/1556-4029.13462
|View full text |Cite
|
Sign up to set email alerts
|

Using Carbon, Oxygen, Strontium, and Lead Isotopes in Modern Human Teeth for Forensic Investigations: A Critical Overview Based on Data from Bulgaria

Abstract: Isotopic data obtained from human remains can provide information about an individual's origin, migration, and diet. We evaluate the usefulness of carbon, oxygen, strontium, and lead isotopes for forensic investigations by comparing data from Bulgarian teeth with data from other regions. Geo-referencing based on oxygen or strontium isotopes can be misleading due to overlap with other countries in Europe and other continents. Carbon and lead isotopes, in combination with oxygen and strontium isotopes, provide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 35 publications
(110 reference statements)
4
37
0
Order By: Relevance
“…tissue) [67]. Thus, Sr isotope analysis of human tissues can be used to reconstruct the potential travel movement history of individuals [22,68,69] through comparison of measured 87 Sr/ 86 Sr ratios in a sample to published Sr isoscapes or other reference sample datasets.…”
Section: Isotopes Used For Human Provenancingmentioning
confidence: 99%
See 1 more Smart Citation
“…tissue) [67]. Thus, Sr isotope analysis of human tissues can be used to reconstruct the potential travel movement history of individuals [22,68,69] through comparison of measured 87 Sr/ 86 Sr ratios in a sample to published Sr isoscapes or other reference sample datasets.…”
Section: Isotopes Used For Human Provenancingmentioning
confidence: 99%
“…However, additional reference datasets of Pb isotopic variations in human tissues are available, e.g. [29,69,73,74]. Like Sr, Pb can substitute for calcium in bone and teeth and there is generally no isotopic fractionation between element source and human tissue.…”
Section: Isotopes Used For Human Provenancingmentioning
confidence: 99%
“…Publication of isotope data from different human populations provides an opportunity to create amalgamated data sets (e.g., Pollard et al 2011;Lightfoot and O'Connell 2016;Someda et al 2016;Kamenov and Curtis 2017). Unfortunately, adequate assessment of comparability is not always undertaken before isotope data from the anthropological, archaeological and/or forensic literature are directly compiled.…”
Section: Background To Human Identification Using Isotopic Analysismentioning
confidence: 99%
“…; Lightfoot and O'Connell ; Someda et al . ; Kamenov and Curtis ). Unfortunately, adequate assessment of comparability is not always undertaken before isotope data from the anthropological, archaeological and/or forensic literature are directly compiled.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of sex is an important first step in the identification process of an individual in a forensic examination. A biological profile which includes age, race, and stature when determined from the various human remains are amongst several other key parameters that need to be rapidly determined [ 1 2 ]. Reports from previous studies have indicated that virtually every human bone has been used for sex determination with varying accuracy rates [ 3 4 ].…”
Section: Introductionmentioning
confidence: 99%